Analysing transitions in intimate relationships with panel data - Michael Feldhaus; Richard Preetz (Comparative Population Studies (CPoS), 2021)
Panel data on intimate relationships are becoming increasingly available, enabling a closer examination and deeper understanding of why and how they develop over time. The aim of this review is to illustrate to what extent demographic research has made progress in understanding the dynamics of intimate relationships by examining panel data. We focus on hypotheses about key transitions throughout the progression of intimate relationships, ranging from union formation up to cohabitation, marriage, divorce and repartnering. For every hypothesis, we will present findings from cross-sectional data and illustrate whether the use of panel data and longitudinal methods modified the previous understandings of transitions in intimate relationships.
urn:nbn:de:bib-cpos-2021-12en9
Keywords: 300; Cohabitation; Divorce; Intimate relationships; Life course transitions; Marriage; Panel data